DEVELOPMENT OF BUSAKBAR MEDIA (CULTURAL DIVERSITY POCKET BOOK BASED ON AUGMENTED REALITY) TO ENHANCE STUDENTS’ LEARNING INTEREST IN PANCASILA EDUCATION FOR FIFTH-GRADE ELEMENTARY STUDENTS - Vinda Wahyu Pandhini; Syifaul Mawaddah; Shefira Mahardhika Nursahid; Komariyah; Fahrur Rozi; Ellianawat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop and validate BUSAKBAR (Cultural Diversity PocketBook Based on Augmented Reality) as an innovative learning medium to enhancefifth-grade students’ interest in learning Pancasila Education. The study applies aResearch and Development (R&D) approach using the ADDIE model Analysis,Design, Development, Implementation, and Evaluation. Data were collectedthrough questionnaires, expert validations, and pre- and post-tests. The findingsrevealed that the BUSAKBAR media achieved high validity, with the materialexpert evaluation reaching 87.5% and the media expert evaluation reaching91.23%, both categorized as highly feasible. Classroom implementationdemonstrated a 47% improvement in learning interest from the pre-cycle to thefirst cycle, with 88% of students categorized as having high or very high learninginterest. The novelty of this study lies in integrating Augmented Reality (AR)technology into a portable pocket book format specifically designed for PancasilaEducation an area that has received limited attention in previous researchcompared to science and mathematics subjects. BUSAKBAR combines visualinteractivity, cultural representation, and character education aligned with thePancasila Student Profile within the Merdeka Curriculum. This innovation providesa practical and engaging learning tool that bridges traditional print-based anddigital learning environments. Therefore, BUSAKBAR can be considered a validand effective medium to foster students’ learning motivation and appreciation ofIndonesia’s cultural diversity.Keywords: Augmented Reality, BUSAKBAR, Learning Interest, PancasilaEducation Innovation